Evidence for Deformation in the Cambrian‐Ordovician Warburton Basin and Implications for the Evolution of the Tasmanides (Eastern Australia). Issue 5 (2nd May 2019) - Abdullah, Rashed; Nugroho, Rio; Rosenbaum, Gideon; Doublier, Michael P.; Shaanan, Uri; Zwingmann, Horst
Abstract: The Paleozoic tectonic history of the Tasmanides in eastern Australia was dominated by subduction‐related processes along the margin of eastern Gondwana. The earliest deformation event, Delamerian Orogeny, took place in the middle‐late Cambrian and is recorded in rocks within the Delamerian and Thomson orogens. The Cambrian‐Ordovician Warburton Basin covers the boundary between the Delamerian and Thomson Orogens, but very little is known about its origin and deformation history. Here we interpret geophysical data, including 2‐D seismic reflection transects, Bouguer gravity, and aeromagnetic data that provide new insights into the deformation in the eastern Warburton Basin and the kinematics of major faults. Our results show that curvilinear NE‐trending faults in the eastern Warburton Basin are basement reverse faults that experienced multiple phases of contractional deformation. Evidence for a syn‐kinematic Cambrian package (Kalladeina Formation) suggests that faulting commenced in response to the Delamerian Orogeny. A subsequent Early Devonian deformation in the eastern Warburton Basin is evident from K‐Ar geochronology of low‐grade (subgreenschist) metasedimentary rocks. We suggest that the NE‐trending Cambrian fold‐thrust belt within the eastern Warburton Basin marks the continuation of the curved Delamerian Orogen into the Thomson Orogen. This oroclinal structure may have developed in the Early Devonian in response to dextral transpression along the northern boundary of the Delamerian Orogen. Our results provide a demonstration for the complex interactions that can take place during the evolution of convergent plate boundaries, involving deformation in the fold‐thrust belt, development of sedimentary basins, and oroclinal bending. Key Points: We present new evidence for the northern continuation of the Ross‐Delamerian Orogen A Cambrian fold‐thrust belt in the eastern Warburton Basin was active during the Delamerian Orogeny The orogen is strongly curved, possibly in response to Early Devonian dextral transpression